Perancangan Strategi Pemasaran Guna Meningkatkan Volume Penjualan Produk Mebel Menggunakan Analisis SWOT dan QSPM” (Studi Kasus di UD. Andika, Sidotani) - Andika, Rizki; Sutrisno, Sutrisno; Polewangi, Yudi Daeng (Universitas Medan Area, 2024)
UMKM UD. Andika is a furniture craftsman located in Sidotani Village, Bandar District, Simalungun Regency. This UMKM operates in the furniture industry with furniture products for doors, windows, cabinets, chairs and others. Furniture craftsmen must arrange marketing strategies that are considered appropriate to face competition in the market and must be able to analyze and anticipate environmental changes, both internally and externally. The research aims to identify internal and external factors. The use of SWOT (Strength, Weakness, Opportunity, Threat) and QSPM (Quantitative Strategic Planning Matrix) methods to determine the right company strategy in identifying optimal areas is very important for the development of the company's next strategy. The results showed that the SWOT analysis obtained 8 marketing strategies, namely maintaining quality, being more active in technology, improving management skills, maintaining an image, increasing the number of employees, maintaining excellence, implementing a digital marketing system, following trends in design and innovation. While in the QSPM analysis, the preferred strategy is to implement a digital marketing system in order to compete with new competitors.